Infrared ultra-wideband high-absorption device and preparation method and application thereof
By forming a three-dimensional conical microstructure on the surface of the semiconductor matrix and growing a carbon-based material absorption layer, the problems of complexity and high cost of preparation of existing infrared wide band absorbing devices are solved, and high absorption rate and large-area preparation of infrared ultra-wide band are achieved.
Patent Information
- Application Number
- CN202510677024.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-23
- Publication Date
- 2025-09-02
AI Technical Summary
The preparation of existing infrared wide band absorbing devices has problems such as excessive thickness of the absorber film layer, low duty cycle, complex structure, high production cost, complex preparation process, and poor adhesion between materials and substrates, making it difficult to achieve large area, low cost and rapid preparation.
Wet corrosion is used to form multiple three-dimensional conical microstructures on the surface of the semiconductor substrate, and a carbon-based material absorption layer is grown on its surface. A specific thickness of olefinic carbon material is grown on the conical structure by chemical vapor deposition method to form an infrared ultra-wide band high-absorbing device.
It achieves high absorption rate in the infrared 1.5μm~16μm band, is low-cost, simple process, easy to prepare on a large scale, and is suitable for multi-scenario applications.
Smart Images

Figure CN120577903A_ABST
Abstract
Description
Technical Field
[0001] The present invention particularly relates to an infrared ultra-wideband high absorption device and a preparation method and application thereof, belonging to the field of micro-nano manufacturing technology. Background Art
[0002] Wideband infrared absorption holds a crucial position in modern science and technology, with broad applications in areas such as radiative cooling, optical sensing, infrared detection and imaging, and infrared photothermal therapy. In military applications, infrared detection and imaging technology plays an irreplaceable role in military reconnaissance, target identification and tracking, security monitoring, and medical diagnosis.
[0003] In the design and preparation of infrared broadband absorbers, broadband absorption is usually achieved by designing multi-layer thin film stack resonant cavity structures, growing vertical carbon nanotube arrays, and designing metamaterial resonant structures with different periodic structures. In the actual preparation of such broadband absorption devices, there are practical difficulties such as excessively thick absorber film layers, low duty cycle, complex structure, high production cost, complex preparation process, and poor adhesion between the material and the substrate. Metamaterials are artificially designed structures that can obtain the required dielectric constant or magnetic permeability by adjusting the geometry and its size. They usually combine multiple subwavelength sizes to achieve multiple surface plasmon resonances to increase the absorption bandwidth. However, this structural system is complex, the preparation process requirements are extremely high, and it cannot achieve high absorption in the ultra-broad infrared band. Due to the limitations of the photolithography process, it is difficult to achieve large-scale, fast, and low-cost preparation, and there are still challenges in practical application.
[0004] Currently, most of the preparation technologies for infrared broadband absorbers focus on multilayer thin film stack structures, carbon-based material structure design, and metamaterial structure design. For example, Carbon 161, 510e516, 2020 and Science Advances. 9, eade4853, 2023 proposed a method of extracting a single layer of super-aligned carbon nanotube (SACNT) film from a 300μm high carbon nanotube array grown on an 8-inch silicon wafer. Two layers of mutually perpendicular suspended SACNT films were then assembled on a metal frame. Subsequently, a third layer of SACNT film was placed on the grid at approximately 45 degrees relative to the underlying SACNT grid. This method can be used to prepare a super-aligned carbon nanotube film network with high penetration on a variety of substrates, forming an absorber with an absorption efficiency of more than 99% over a wide spectral range of 250nm to 20μm. However, this method requires the growth of high-quality vertically arrayed carbon nanotubes and the need to pull out high-quality super-aligned carbon nanotube films, which is technically difficult. In addition, the film has poor adhesion to the supporting substrate and is not suitable for the needs of special application environments. Science Advances.9, eade4853, 2023 reported a method for fabricating a non-periodic array of conical microcavity master templates on a CR-39 plastic template using ion track etching. The master template pattern was then transferred to a PDMS replica mold, which was then stamped onto a black absorber material to achieve pattern transfer. This resulted in an absorber device with a hemispherical absorptivity exceeding 99.98% in the 200nm to 2μm spectral range. However, this technique requires specialized ion track etching equipment to prepare the master plate and requires multiple mold repetitions to complete the absorber fabrication. This complex process prevents large-scale fabrication at low cost. Summary of the Invention
[0005] The main purpose of the present invention is to provide an infrared ultra-wideband high absorption device and its preparation method and application, so as to overcome the shortcomings of the prior art.
[0006] To achieve the aforementioned object of the invention, the technical solutions adopted by the present invention include:
[0007] A first aspect of an embodiment of the present invention provides an infrared ultra-wide band high absorption device, comprising: a semiconductor substrate and a carbon-based material absorption layer, the active surface of the semiconductor substrate having a plurality of three-dimensional conical microstructures, the carbon-based material absorption layer being covered on the surface of the three-dimensional conical microstructures, the height and / or bottom side length of the three-dimensional conical microstructures being 1 μm to 15 μm, and the thickness of the carbon-based material absorption layer being 100 nm to 3 μm.
[0008] The second aspect of an embodiment of the present invention provides a method for preparing the infrared ultra-wide band high absorption device, which includes: forming a plurality of three-dimensional conical microstructures on the active surface of a semiconductor substrate, and forming a carbon-based material absorption layer on the surface of the plurality of three-dimensional conical microstructures.
[0009] A third aspect of an embodiment of the present invention provides the use of the infrared ultra-wideband high absorption device in the fields of radiation cooling, optical sensing, infrared detection and imaging, or infrared photothermal therapy.
[0010] Compared with the prior art, the advantages of the present invention include:
[0011] The present invention provides a method for preparing an infrared broadband absorption device, wherein a conical structure is prepared on an intrinsic silicon surface with a (100) crystal orientation by wet etching or other methods, and then a specific thickness of olefinic carbon material is grown on the conical structure by chemical vapor deposition (CVD) or other methods to obtain an infrared broadband absorber. The prepared infrared broadband absorption device has low cost, simple process, reliable performance, and is easy to achieve large-area preparation and multi-scenario application. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 This is a schematic structural diagram of an infrared ultra-wideband high absorption device provided in a typical embodiment of the present invention;
[0013] Figure 2a 、 Figure 2b They are respectively a top view and a side view of a silicon substrate having a series of cone-shaped structures formed thereon after wet etching in a typical embodiment of the present invention;
[0014] Figure 3a 、 Figure 3b This is an SEM image of a typical embodiment of the present invention after forming an olefinic carbon material on the surface of a conical structure of a silicon substrate;
[0015] Figure 4 This is the absorption spectrum of an infrared ultra-wideband high absorption device in the infrared band of 1.5μm to 16μm provided in Example 1, Example 2, and Example 3, a typical implementation case of the present invention. DETAILED DESCRIPTION
[0016] In view of the shortcomings of the prior art, the inventors of this case, after long-term research and extensive practice, have proposed the technical solution of the present invention. The following will further explain this technical solution, its implementation process and principles.
[0017] The present invention discloses an infrared ultra-wide band absorption device prepared by a two-step method. First, a wet chemical etching method is used to form a micron-scale conical structure of random size on a silicon surface with a (100) crystal orientation. Subsequently, a carbon-based material of a specific thickness is grown on the conical structure to achieve high absorption of the infrared ultra-wide band of 1.5μm to 16μm. There is no need to design complex film structure preparation and metamaterial design and expensive processing technology as well as complex carbon-based material structure design. The present invention has the outstanding advantages of large-scale preparation, ultra-low cost, simple and fast process, no metal materials, and can achieve infrared ultra-wide band absorption.
[0018] A first aspect of an embodiment of the present invention provides an infrared ultra-wideband high absorption device, comprising: a semiconductor substrate and a carbon-based material absorption layer, wherein the active surface of the semiconductor substrate has a plurality of three-dimensional conical microstructures, and the carbon-based material absorption layer is covered on the surface of the three-dimensional conical microstructures, the height and / or bottom surface length of the three-dimensional conical microstructures is 1 μm to 15 μm, and the thickness of the carbon-based material absorption layer is 100 nm to 3 μm.
[0019] Furthermore, the geometric parameters of the three-dimensional conical microstructures are in a non-deterministic distribution, and the geometric parameters of the three-dimensional conical microstructures include height and bottom side length.
[0020] Furthermore, the three-dimensional conical microstructure is a quadrangular pyramid structure.
[0021] Furthermore, the height and bottom side length of the three-dimensional conical microstructure are in the micrometer scale.
[0022] Furthermore, the plurality of three-dimensional conical microstructures are closely arranged.
[0023] Furthermore, the active surface is completely covered by the plurality of three-dimensional conical microstructures.
[0024] Furthermore, the semiconductor substrate is a silicon substrate with a (100) crystal orientation, and the three-dimensional conical microstructure is formed by in-situ processing of the semiconductor substrate using dry etching or wet etching. The bottom surface of the three-dimensional conical microstructure is a (100) crystal plane, and the side surface is a (111) crystal plane. Exemplarily, the three-dimensional conical microstructure can be formed by processing using reactive ion etching (RIE), inductively coupled plasma etching (ICP), or alkaline solution etching.
[0025] Furthermore, the carbon-based material absorption layer completely covers the plurality of three-dimensional conical microstructures.
[0026] Furthermore, the carbon-based material absorption layer continuously covers the surfaces of the plurality of three-dimensional conical microstructures.
[0027] Furthermore, the carbon-based material contained in the carbon-based material absorption layer is deposited in a granular form on the surface of the three-dimensional conical microstructure.
[0028] Furthermore, the material of the carbon-based material absorption layer includes at least one of olefinic carbon materials, graphene, and carbon nanotubes, but is not limited thereto.
[0029] Furthermore, the particle size of the carbon-based material particles contained in the carbon-based material absorption layer is 20 nm to 300 nm.
[0030] Furthermore, the infrared ultra-wideband high absorption device has an average absorption rate of more than 95% for infrared light in the range of 1.5 μm to 16 μm.
[0031] The second aspect of an embodiment of the present invention provides a method for preparing the infrared ultra-wide band high absorption device, which includes: forming a plurality of three-dimensional conical microstructures on the active surface of a semiconductor substrate, and forming a carbon-based material absorption layer on the surface of the plurality of three-dimensional conical microstructures.
[0032] Furthermore, the preparation method of the infrared ultra-wide band high absorption device includes: in-situ processing to form a plurality of the three-dimensional conical microstructures on the active surface of the semiconductor substrate, or first preparing a template having a plurality of the three-dimensional conical microstructures, and then casting the template onto the active surface of the semiconductor substrate.
[0033] Furthermore, the preparation method includes: forming a plurality of the three-dimensional conical microstructures in situ on the active surface of the semiconductor substrate by dry etching or wet etching.
[0034] Furthermore, the semiconductor substrate is a silicon substrate with a (100) crystal orientation, and the preparation method includes: immersing the silicon substrate with a (100) crystal orientation in an alkaline etching solution for 30 minutes to 50 minutes, thereby forming a plurality of three-dimensional conical microstructures with non-deterministic distribution of geometric parameters.
[0035] Furthermore, the preparation method of the infrared ultra-wide band high absorption device includes: growing a carbon-based material by chemical vapor deposition or physical vapor deposition, and making the carbon-based material uniformly deposited in a granular form on the surface of multiple three-dimensional conical microstructures, thereby forming the carbon-based material absorption layer.
[0036] A third aspect of an embodiment of the present invention provides the use of the infrared ultra-wideband high absorption device in the fields of radiation cooling, optical sensing, infrared detection and imaging, or infrared photothermal therapy.
[0037] The following will further explain the technical solution, its implementation process and principles with reference to specific implementation cases.
[0038] In a typical implementation, see Figure 1 , an infrared ultra-wide band high absorption device, comprising a semiconductor substrate and a carbon-based material absorption layer, wherein the active surface of the semiconductor substrate has a plurality of three-dimensional conical microstructures, and the geometric parameters of the plurality of three-dimensional conical microstructures are non-deterministically distributed, and the carbon-based material absorption layer is covered on the surface of the three-dimensional conical microstructure, wherein the height and / or bottom side length of the three-dimensional conical microstructure is 1μm to 15μm, and the thickness of the carbon-based material absorption layer is 100nm to 3μm.
[0039] It should be noted that the geometric parameters of the three-dimensional conical microstructures are non-deterministically distributed, meaning that the sizes of the three-dimensional conical microstructures are random. The geometric parameters of the three-dimensional conical microstructures include height and base length. As a typical example, the three-dimensional conical microstructures are quadrangular pyramid structures.
[0040] Specifically, the plurality of three-dimensional conical microstructures are closely arranged, and the active surface is completely covered by the plurality of three-dimensional conical microstructures. When the semiconductor substrate is a silicon substrate with a (100) crystal orientation, the three-dimensional conical microstructure can be formed by in-situ processing of the semiconductor substrate using dry etching or wet etching, and the bottom surface of the three-dimensional conical microstructure is a (100) crystal plane and the side surface is a (111) crystal plane. Exemplarily, the three-dimensional conical microstructure can be formed by processing using reactive ion etching (RIE), inductively coupled plasma etching (ICP), or alkaline solution etching.
[0041] Specifically, the carbon-based material absorption layer completely covers the multiple three-dimensional conical microstructures. More specifically, the carbon-based material absorption layer continuously covers the surfaces of the multiple three-dimensional conical microstructures, wherein the carbon-based material contained in the carbon-based material absorption layer is accumulated in granular form on the surface of the three-dimensional conical microstructure. The material of the carbon-based material absorption layer includes at least one of olefinic carbon material, graphene, and carbon nanotubes, but is not limited thereto. The particle size of the carbon-based material particles contained in the carbon-based material absorption layer is 20nm to 300nm.
[0042] Specifically, the present invention has discovered through testing that the intrinsic absorption properties of carbon-based materials produce a light-trapping effect in three-dimensional conical microstructures. The uneven distribution of these three-dimensional conical microstructures can effectively reduce specular reflection in devices, thereby enhancing the carbon-based material's absorption. A carbon-based material of a specific thickness, combined with three-dimensional conical microstructures of specific dimensions, can achieve ultra-high absorption across a wide infrared band. Changing the shape and / or geometric dimensions of the three-dimensional conical microstructures increases the device's surface reflection and narrows its absorption wavelength range.
[0043] In a typical embodiment, a method for preparing an ultra-wideband infrared high absorption device comprises the following steps:
[0044] 1) Prepare a silicon substrate with a conical structure.
[0045] A. Cutting a 500 μm thick, double-sided polished (100) crystalline silicon substrate into 2 cm*2 cm pieces, and then ultrasonically cleaning the silicon substrate in acetone, ethanol, and deionized water for 30 minutes, and then drying it with a nitrogen gun for later use;
[0046] B. Prepare an alkaline solution containing isopropyl alcohol (IPA, 6.5 wt %) and sodium hydroxide (NaOH, 1.5 wt %) in deionized water (DI);
[0047] C. Soak the cleaned silicon substrate in the alkaline solution for 30-50 minutes to form a series of unevenly sized conical structures (i.e., the aforementioned three-dimensional conical microstructures, the same below) on the surface of the silicon substrate. Figure 2a 、 Figure 2b As shown, the bottom surface of the cone structure is the (100) crystal plane, the side surface is the (111) crystal plane, and the height and bottom side length of the cone structure are 1 μm to 15 μm;
[0048] D. Take out the corroded silicon substrate, clean it with deionized water ultrasonically for 10 minutes, and then blow it dry with a nitrogen gun to complete the silicon substrate preparation.
[0049] 2) Growth of carbon-based material absorption layer.
[0050] A. Place the etched silicon substrate into a quartz boat and send it into a chemical vapor deposition furnace;
[0051] B. Argon (Ar) and hydrogen (H2) are introduced into a chemical vapor deposition furnace at a flow rate ratio of 3:1. At the same time, ethylene (C2H4) and other olefinic carbon materials are introduced as a carbon source at a flow rate of 10 sccm to 40 sccm.
[0052] C. Set the growth temperature to 750℃~900℃, keep it warm for 15min~120min after reaching the temperature, and form a layer of carbon-based material as a carbon-based material absorption layer on the surface of the cone structure on the silicon substrate. The thickness of the carbon-based material absorption layer is 100nm~3μm. Figure 3a 、 Figure 3b As shown, the carbon-based material is accumulated in granular form on the surface of the cone structure;
[0053] D. After the sample growth is completed, the CVD furnace is naturally cooled to room temperature and the sample is taken out to complete the preparation. The final infrared ultra-wideband high absorption device is as follows Figure 1 shown.
[0054] Depend on Figure 2a 、 Figure 2b and Figure 3a 、 Figure 3b It can be seen that after wet etching, a micron-scale, uneven-sized conical structure is formed on the surface of the silicon substrate. The introduction of the uneven-sized conical structure can effectively achieve anti-reflection effect in a wide infrared band, so that the olefinic carbon material with a specific thickness and a granular structure can further reduce the reflection and scattering of the incident light, thereby achieving a high absorption effect in a wide infrared band.
[0055] Example 1
[0056] A method for preparing an ultra-wideband infrared high absorption device, specifically comprising:
[0057] 1) A 500 μm thick, double-sided polished (100) crystalline intrinsic silicon substrate was cut into 2 cm*2 cm silicon substrates, and the silicon substrates were sequentially placed in acetone, ethanol and deionized water for ultrasonic cleaning for 30 minutes and then blown dry with a nitrogen gun.
[0058] 2) Prepare an alkaline solution of deionized water (DI) containing isopropyl alcohol (IPA, 6.5wt%) and sodium hydroxide (NaOH, 1.5wt%) and place it in an 85°C oil bath. Immerse the cleaned double-polished silicon substrate in the solution and etch it for 30 minutes. Then, rinse the etched sample with deionized water and blow dry it for later use.
[0059] 3) Place the corroded silicon substrate in a quartz boat and send it into a chemical vapor deposition (CVD) furnace. Introduce argon (Ar) and hydrogen (H2) into the chemical vapor deposition (CVD) furnace. The flow rates of argon (Ar) and hydrogen (H2) are 300 sccm and 100 sccm, respectively. At the same time, introduce ethylene (C2H4) into the chemical vapor deposition (CVD) furnace at a flow rate of 10 sccm. Set the growth temperature in the chemical vapor deposition (CVD) furnace to 800°C. After reaching the temperature, keep it warm for 15 minutes. A carbon-based material with a thickness of 100 nm is formed on the surface of the conical structure on the silicon substrate as an absorption layer. After the sample growth is completed, the CVD furnace is naturally cooled to room temperature and the sample is taken out to complete the preparation.
[0060] Example 2
[0061] A method for preparing an ultra-wideband infrared high absorption device, specifically comprising:
[0062] 1) A 500 μm thick, double-sided polished (100) crystalline intrinsic silicon substrate was cut into 2 cm*2 cm silicon substrates, and the silicon substrates were sequentially placed in acetone, ethanol and deionized water for ultrasonic cleaning for 30 minutes and then blown dry with a nitrogen gun.
[0063] 2) Prepare an alkaline solution of deionized water (DI) containing isopropyl alcohol (IPA, 6.5wt%) and sodium hydroxide (NaOH, 1.5wt%) and place it in an 85°C oil bath. Immerse the cleaned double-polished silicon substrate in the solution and etch it for 40 minutes. Then, rinse the etched sample with deionized water and blow dry it for later use.
[0064] 3) Place the corroded silicon substrate in a quartz boat and send it into a chemical vapor deposition (CVD) furnace. Introduce argon (Ar) and hydrogen (H2) into the chemical vapor deposition (CVD) furnace. The flow rates of argon (Ar) and hydrogen (H2) are 300 sccm and 100 sccm, respectively. At the same time, introduce ethylene (C2H4) into the chemical vapor deposition (CVD) furnace at a flow rate of 25 sccm. Set the growth temperature in the chemical vapor deposition (CVD) furnace to 800°C. After reaching the temperature, keep it warm for 60 minutes. Form a carbon-based material with a thickness of 1000 nm as an absorption layer on the surface of the conical structure on the silicon substrate. After the sample growth is completed, the CVD furnace is naturally cooled to room temperature and the sample is taken out to complete the preparation.
[0065] Example 3
[0066] A method for preparing an ultra-wideband infrared high absorption device, specifically comprising:
[0067] 1) A 500 μm thick, double-sided polished (100) crystalline intrinsic silicon substrate was cut into 2 cm*2 cm silicon substrates, and the silicon substrates were sequentially placed in acetone, ethanol and deionized water for ultrasonic cleaning for 30 minutes and then blown dry with a nitrogen gun.
[0068] 2) Prepare an alkaline solution of deionized water (DI) containing isopropyl alcohol (IPA, 6.5wt%) and sodium hydroxide (NaOH, 1.5wt%) and place it in an 85°C oil bath. Immerse the cleaned double-polished silicon substrate in the solution and etch it for 50 minutes. Then, rinse the etched sample with deionized water and blow dry it for later use.
[0069] 3) Place the corroded silicon substrate in a quartz boat and send it into a chemical vapor deposition (CVD) furnace. Introduce argon (Ar) and hydrogen (H2) into the chemical vapor deposition (CVD) furnace. The flow rates of argon (Ar) and hydrogen (H2) are 300 sccm and 100 sccm, respectively. At the same time, introduce ethylene (C2H4) into the chemical vapor deposition (CVD) furnace at a flow rate of 40 sccm. Set the growth temperature in the chemical vapor deposition (CVD) furnace to 800°C. After reaching the temperature, keep it warm for 120 minutes. Form a carbon-based material with a thickness of 3 μm as an absorption layer on the surface of the conical structure on the silicon substrate. After the sample growth is completed, the CVD furnace is naturally cooled to room temperature and the sample is taken out to complete the preparation.
[0070] Comparative Example 1
[0071] A method for preparing an infrared band absorption device, specifically comprising:
[0072] 1) A 500 μm thick, double-sided polished (100) crystalline intrinsic silicon substrate was cut into 2 cm*2 cm silicon substrates, and the silicon substrates were sequentially placed in acetone, ethanol and deionized water for ultrasonic cleaning for 30 minutes and then blown dry with a nitrogen gun.
[0073] 2) A periodically arranged cone structure was prepared on a silicon substrate using ultraviolet lithography and dry etching methods. The cone structure had a bottom diameter of 3 μm and a height of 3 μm.
[0074] 3) The dry-etched silicon substrate was placed in a quartz boat and sent into a chemical vapor deposition (CVD) furnace. Argon (Ar) and hydrogen (H2) were introduced into the chemical vapor deposition (CVD) furnace. The flow rates of argon (Ar) and hydrogen (H2) were 300 sccm and 100 sccm, respectively. At the same time, ethylene (C2H4) was introduced into the chemical vapor deposition (CVD) furnace at a flow rate of 10 sccm. The growth temperature in the chemical vapor deposition (CVD) furnace was set to 800°C. After reaching the temperature, it was kept warm for 15 minutes to form a carbon-based material with a thickness of 100 nm as an absorption layer on the surface of the conical structure on the silicon substrate.
[0075] Comparative Example 2
[0076] A method for preparing an infrared band absorption device, specifically comprising:
[0077] 1) A 500 μm thick, double-sided polished (100) crystalline intrinsic silicon substrate was cut into 2 cm*2 cm silicon substrates, and the silicon substrates were sequentially placed in acetone, ethanol and deionized water for ultrasonic cleaning for 30 minutes and then blown dry with a nitrogen gun.
[0078] 2) Prepare an alkaline solution of deionized water (DI) containing isopropyl alcohol (IPA, 6.5wt%) and sodium hydroxide (NaOH, 1.5wt%) and place it in an 85°C oil bath. Immerse the cleaned double-polished silicon substrate in the solution and etch it for 40 minutes. Then, rinse the etched sample with deionized water and blow dry it for later use.
[0079] 3) Place the etched silicon substrate in a quartz boat and send it into a chemical vapor deposition (CVD) furnace. Introduce argon (Ar) and hydrogen (H2) into the chemical vapor deposition (CVD) furnace. The flow rates of argon (Ar) and hydrogen (H2) are 300 sccm and 100 sccm, respectively. At the same time, introduce ethylene (C2H4) into the chemical vapor deposition (CVD) furnace at a flow rate of 10 sccm. Set the growth temperature in the chemical vapor deposition (CVD) furnace to 800°C. After reaching the temperature, keep it warm for 5 minutes to form a 90 nm thick ethylene material as an absorption layer on the surface of the conical structure on the silicon substrate. After the sample growth is completed, the CVD furnace is naturally cooled to room temperature and the sample is taken out to complete the preparation.
[0080] Comparative Example 3
[0081] A method for preparing an infrared band absorption device, specifically comprising:
[0082] 1) A 500 μm thick, double-sided polished (100) crystalline intrinsic silicon substrate was cut into 2 cm*2 cm silicon substrates, and the silicon substrates were sequentially placed in acetone, ethanol and deionized water for ultrasonic cleaning for 30 minutes and then blown dry with a nitrogen gun.
[0083] 2) Prepare an alkaline solution of deionized water (DI) containing isopropyl alcohol (IPA, 6.5wt%) and sodium hydroxide (NaOH, 1.5wt%) and place it in an 85°C oil bath. Immerse the cleaned double-polished silicon substrate in the solution and etch it for 50 minutes. Then, rinse the etched sample with deionized water and blow dry it for later use.
[0084] 3) The etched silicon substrate was placed in a quartz boat and sent into a chemical vapor deposition (CVD) furnace. Argon (Ar) and hydrogen (H2) were introduced into the chemical vapor deposition (CVD) furnace at flow rates of 300 sccm and 100 sccm, respectively. At the same time, ethylene (C2H4) was introduced into the chemical vapor deposition (CVD) furnace at a flow rate of 40 sccm. The growth temperature in the chemical vapor deposition (CVD) furnace was set to 800°C. After reaching the temperature, the temperature was kept for 130 minutes to form an ethylene material with a thickness of 3.1 μm as an absorption layer on the surface of the conical structure on the silicon substrate. After the sample growth was completed, the CVD furnace was naturally cooled to room temperature and the sample was taken out to complete the preparation.
[0085] The absorption spectra of the infrared ultra-wideband high absorption devices obtained in Examples 1 to 3 of the present invention are as follows: Figure 4As shown, it can be seen that the device in this embodiment of the present invention has an average absorptivity of approximately 95% in the 1.5μm to 16μm infrared band, showing excellent absorption characteristics. This proves that by further controlling the wet etching time and the growth conditions of the carbon-based material, the present invention can optimize the absorptivity and is expected to increase the absorptivity to over 99%. In Comparative Example 1, the periodic array of conical structures increases reflection, resulting in a narrower infrared light absorption band for the device. In Comparative Example 2, the absorption layer is too thin, resulting in the device being unable to fully absorb the incident light, resulting in a high reflectivity and a significantly lower absorptivity. In Comparative Example 3, the absorption layer is too thick, causing the absorption layer to change the structure of the conical structure, resulting in a high reflectivity and a significantly lower absorptivity.
[0086] The present invention uses silicon with a (100) crystal orientation as a template, and obtains a silicon substrate with a micron-scale conical structure through simple wet etching as a template to grow a carbon-based material of a specific thickness, wherein the carbon-based material is uniformly accumulated on the conical structure in a granular form. The conical micron structure can effectively realize anti-reflection properties. The carbon-based material is used as an absorption material and can effectively realize absorption enhancement in the conical structure, ultimately realizing an infrared wide-band high-absorption device.
[0087] The present invention achieves high absorption in the 1.5μm to 16μm infrared band by growing carbon-based materials on micron-scale conical silicon structures. The preparation method is simple, requiring only wet etching to prepare the conical structure and one CVD growth of carbon-based materials to a specific thickness. The absorption performance can be further improved by optimizing the preparation process.
[0088] The broadband infrared absorption device provided by the present invention is quick, convenient, and cost-effective to manufacture, offering high product reliability. It can also fabricate wafer-scale, highly absorbing infrared bulk structures, enabling diverse applications. Furthermore, the method for fabricating the broadband infrared absorption device provided by the present invention is simple and does not require an additional support substrate.
[0089] It should be understood that the above embodiments are merely illustrative of the technical concepts and features of the present invention. Their purpose is to enable those skilled in the art to understand the contents of the present invention and implement them accordingly. They are not intended to limit the scope of protection of the present invention. Any equivalent variations or modifications made in accordance with the spirit and substance of the present invention are intended to be encompassed within the scope of protection of the present invention.
Claims
1. An infrared ultra-wideband high absorption device, characterized in that: include: A semiconductor substrate and a carbon-based material absorption layer, wherein the active surface of the semiconductor substrate has multiple three-dimensional conical microstructures, the carbon-based material absorption layer is covered on the surface of the three-dimensional conical microstructures, the height and / or bottom side length of the three-dimensional conical microstructures is 1μm to 15μm, and the thickness of the carbon-based material absorption layer is 100nm to 3μm.
2. The ultra-wideband infrared high absorption device according to claim 1, characterized in that: The geometric parameters of the three-dimensional conical microstructures are in a non-deterministic distribution, and the geometric parameters of the three-dimensional conical microstructures include height and bottom side length; Preferably, the three-dimensional conical microstructure is a quadrangular pyramid structure; Preferably, the height and bottom side length of the three-dimensional conical microstructure are in the micrometer scale.
3. The ultra-wideband infrared high absorption device according to claim 1 or 2, characterized in that: The plurality of three-dimensional conical microstructures are closely arranged; Preferably, the active surface is completely covered by a plurality of the three-dimensional conical microstructures; Preferably, the semiconductor substrate is a silicon substrate with a (100) crystal orientation, and the three-dimensional conical microstructure is formed by in-situ processing of the semiconductor substrate using dry etching or wet etching. The bottom surface of the three-dimensional conical microstructure is a (100) crystal plane, and the side surface is a (111) crystal plane.
4. The ultra-wideband infrared high absorption device according to claim 1, characterized in that: The carbon-based material absorption layer completely covers the plurality of three-dimensional conical microstructures; Preferably, the carbon-based material absorption layer continuously covers the surfaces of the plurality of three-dimensional conical microstructures; Preferably, the carbon-based material contained in the carbon-based material absorption layer is deposited in a granular form on the surface of the three-dimensional conical microstructure.
5. The ultra-wideband infrared high absorption device according to claim 1 or 4, characterized in that: The material of the carbon-based material absorption layer includes at least one of olefinic carbon materials, graphene, and carbon nanotubes; And / or, the particle size of the carbon-based material particles contained in the carbon-based material absorption layer is 20 nm to 300 nm.
6. The ultra-wideband infrared high absorption device according to claim 1, characterized in that: The infrared ultra-wide band high absorption device has an average absorption rate of more than 95% for infrared band light in the range of 1.5 μm to 16 μm.
7. The method for preparing an ultra-wideband infrared high absorption device according to any one of claims 1 to 7, characterized in that: include: A plurality of three-dimensional cone-shaped microstructures are formed on the active surface of the semiconductor substrate, and a carbon-based material absorption layer is formed on the surfaces of the plurality of three-dimensional cone-shaped microstructures.
8. The method for preparing an ultra-wideband infrared high absorption device according to claim 7, characterized in that: include: In-situ processing forms a plurality of the three-dimensional conical microstructures on the active surface of the semiconductor substrate, or first prepares a template having the plurality of the three-dimensional conical microstructures, and then casts the template onto the active surface of the semiconductor substrate; Preferably, the preparation method comprises: forming a plurality of the three-dimensional conical microstructures in situ on the active surface of the semiconductor substrate by dry etching or wet etching; Preferably, the semiconductor substrate is a silicon substrate with a (100) crystal orientation, and the preparation method includes: immersing the silicon substrate with a (100) crystal orientation in an alkaline etching solution for 30 minutes to 50 minutes, thereby forming a plurality of three-dimensional conical microstructures with non-deterministic distribution of geometric parameters.
9. The method for preparing an ultra-wideband infrared high absorption device according to claim 7, characterized in that: include: The carbon-based material is grown by chemical vapor deposition or physical vapor deposition, and the carbon-based material is deposited in a granular form on the surfaces of the plurality of three-dimensional conical microstructures, thereby forming the carbon-based material absorption layer.
10. Use of the infrared ultra-wideband high absorption device according to any one of claims 1 to 7 in the fields of radiation cooling, optical sensing, infrared detection and imaging, or infrared photothermal therapy.